Beyond Functionality: Building Value To Essential Oils Products at Indonesia Digital Market Field - Romli, Zainur (Indonesian Journal of Business and Entrepreneurship, 2024)
Background: This study investigates the evolving online marketing skills in the digital marketplace, focusing on essential oil products. These products often face market uncertainty regarding product attribute value. Therefore, it is crucial to identify marketing strategies to drive future entrepreneurial success in the essential oil market.Purpose: This research aims to identify how essential oil product sellers communicate their products to attract consumer interest and preferences in the online market.Design/methodology/approach: The study utilizes digital research methods to elucidate the phenomenon of online markets. Using electronic data consisting of product information written by sellers, this research employs web scraping through Python algorithmic computational techniques for data collection. The digital data collected spans from 2020 to 2023, a period marked by the surge in online shopping activities. The data is analyzed using Text Network Analysis (TNA) to map emerging narrative networks.Findings/Result: Essential oil product sellers not only emphasize the intrinsic value attributes of the products as the primary marketing narrative but also explore the social and symbolic values of the products as online marketing strategies to address uncertainties regarding product standardization and safety.Conclusion: Sellers are concerned about the vulnerability of essential oil product values beyond merely campaigning for the product's benefits. Entities with the authority to provide safety labels play a crucial role in enhancing the product's reputation regarding its social value, such as safety.Originality/value (State of the art): Online marketplaces play a crucial role as a new marketing channel for essential oil products. This is due to the increased accessibility of products to consumers and the growing need for advanced online marketing skills in the future. Keywords: essential oil, online marketplace, marketing skills, value product, product reputation